Carbon Budget and Cycling in Perennially Ice–Covered Lake Untersee, East Antarctica - Marsh, Nicole (Université d'Ottawa / University of Ottawa, 2019)
Perennially ice-covered Lake Untersee is one of the largest (8.7 km2) and deepest (~160 m) freshwater lakes in East Antarctica. Water mass balance of Lake Untersee shows it receives ~ 45% of its annual input from melting of the glacial–wall beneath the ice–cover and ~55% from subglacial meltwater; with loss by sublimation of the ice–cover. The lake floor hosts active photosynthetic microbial mats despite weak irradiance through the ice–cover (<5% PAR). This study aims to characterize the carbon content and its isotopic composition (δ13C and 14C) in the lake–waters and microbial mats to develop a carbon budget in order to define carbon sources and its cycling in the lake ecosystem. The DIC in the oxic and alkaline water column (pH 10.4) is very low and of atmospheric origin (0.3–0.4 ppm, δ13C-DIC = –7 to –10‰, F14C-DIC of 0.41 to 0.60). The organic–C content of microbial mats is 0.857 kg C m–2 and the surface layer has very similar δ13C (–9 to –12‰) to the DIC in the water column. The 14C ages of the top and bottom mat layers range from 9,524 to 10,052 years BP, with the age of the bottom mat layers (12,031–13,049 years BP) corresponding to the inferred timing of formation of the lake. Mass balance shows that the rate of the incoming carbon from both subglacial meltwater and englacial melting (8×10^4 g C y–1) is insufficient to account for the carbon sequestered by the microbial mats (4–8×10^9 gC). This suggests that Lake Untersee developed a summer moat when it initially developed (~12 to 13 kya), which allowed for open–exchange with atmospheric CO2 and replenishment of DIC in the water column. This is supported by a higher growth rate observed in the deepest microbial mats. Since the permanent ice–cover developed, the growth rate has decreased, and given the F14C-DIC and F14C-DOC in oxic waters (14C = 4,119 to 7,079 years BP), Lake Untersee has been well–sealed from atmosphere and the water–column subsequently became starved in carbon. These results demonstrate the capacity of microbial communities to adapt to harsh and shifting conditions in Earth’s most extreme environments.
Keywords: limnology; geochemistry; isotope chemistry